Picking Some News about the Retroviral Vector World from the 9th Symposium of the European Society of Gene Therapy. Issue 1 (2002) - Bagnis, Claude
Abstract : The 9th symposium of the European Society of Gene Therapy (ESGT) organized by Murat Tuncer (President of the Meeting), Bernd Gansbacher (President of the ESGT), and Meral Ozguc (Secretary of the Meeting) took place in Antalya, South Turkey, on 2–4 November 2001. Although the international political context made difficult the coming of some researchers, this symposium has drawn an interesting picture of the works in progress in Europe and in the Mediterranean area.